Peran Kepala Sekolah dalam Supervisi Pendidikan Agama Islam pada Kegiatan Belajar Mengajar di SMA Negeri Bareng Jombang - Istibsjaroh Istibsjaroh; Peni Agustina (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2018)
Supervision is a supervisor activity to improve the management of religious education in schools or madrasah so that the teaching and learning activities condition can be achieved. Supervision is not only done by supervisors, but also school principal. As a supervisor, the principal should be good at researching and determining the conditions are needed for the progress of the school to make education objectives is achieved. SMAN Bareng Jombang, has only 2 teachers of Islamic Religious Education (PAI) who are teaching of 19 classes. Therefore, they need much time and guidance from supervisor in developing and improving the quality of teaching and learning process they have conducted. The result shows that the principal role in supervising Islamic religious education in SMAN Bareng was well implemented. The evidence is the principal has done suprvision as researchers, consultants, facilitators, motivators and pioneers of renewal. Such the technique used is observing classroom or direct observation techniques, and the approach used is a collaborative approach.